Does a renewable fuel standard for biofuels reduce climate costs? - Mads Greaker; Michael Hoel; Knut Einar Rosendahl (Statistics Norway, Research Department, 2012)
Recent contributions have questioned whether biofuels policies actually lead to emissions reductions, and thus lower climate costs. In this paper we make two contributions to the literature. First, we study the market effects of a renewable fuel standard. Opposed to most previous studies we model the supply of fossil fuels taking into account that fossil fuels is a non-renewable resource. Second, we model emissions from land use change explicitly when we evaluate the climate effects of the renewable fuel standard. We find that extraction of fossil fuels most likely will decline initially as a consequence of the standard. Thus, if emissions from biofuels are sufficiently low, the standard will have beneficial climate effects. Furthermore, we find that the standard tends to reduce total fuel (i.e., oil plus biofuels) consumption initially. Hence, even if emissions from biofuels are substantial, climate costs may be reduced. Finally, if only a subset of countries introduce a renewable fuel standard, there will be carbon leakage to the rest of the world. However, climate costs may decline as global extraction of fossil fuels is postponed.
Keywords: H23; Q30; Q42; Q54; 330; Biofuels; Non-renewable resources; Land-use changes; Climate costs